The development of Philippine nationalism and its implication to education - Villanueva, Ines Santos 1907- (1954)
This investigation is concerned with the following problems: 1) To trace the development of Philippine Nationalism under the different regimes; and 2) To determine how much nationalism has affected the aims of the school.